Infective endocarditis in pregnant women without intravenous drug use: a multicentre retrospective case series. (13th August 2022) - Escolà-Vergé, Laura; Rello, Pau; Declerck, Charles; Dubée, Vincent; Rouleau, Fréderic; Duval, Xavier; Habib, Gilbert; Lavie-Badie, Yoan; Martin-Blondel, Guillaume; Porte, Lydie; Bouiller, Kevin; Goehringer, François; et al.
Abstract: Objectives: To describe the clinical features and outcomes of infective endocarditis (IE) in pregnant women who do not inject drugs. Methods: A multinational retrospective study was performed at 14 hospitals. All definite IE episodes between January 2000 and April 2021 were included. The main outcomes were maternal mortality and pregnancy-related complications. Results: Twenty-five episodes of IE were included. Median age at IE diagnosis was 33.2 years (IQR 28.3–36.6) and median gestational age was 30 weeks (IQR 16–32). Thirteen (52%) patients had no previously known heart disease. Sixteen (64%) were native IE, 7 (28%) prosthetic and 2 (8%) cardiac implantable electronic device IE. The most common aetiologies were streptococci ( n  = 10, 40%), staphylococci ( n  = 5, 20%), HACEK group ( n  = 3, 12%) and Enterococcus faecalis ( n  = 3, 12%). Twenty (80%) patients presented at least one IE complication; the most common were heart failure ( n  = 13, 52%) and symptomatic embolism other than stroke ( n  = 4, 16%). Twenty-one (84%) patients had surgery indication and surgery was performed when indicated in 19 (90%). There was one maternal death and 16 (64%) patients presented pregnancy-related complications (11 patients ≥1 complication): 3 pregnancy losses, 9 urgent Caesarean sections, 2 emergency Caesarean sections, 1 fetal death, and 11 preterm births. Two patients presented a relapse during a median follow-up of 3.1 years (IQR 0.6–7.4). Conclusions: Strict medical surveillance of pregnant women with IE is required and must involve a multidisciplinary team including obstetricians and neonatologists. Furthermore, the potential risk of IE during pregnancy should never be underestimated in women with previously known underlying heart disease.